Exploring Mothers’ and Fathers’ Relationships with Sons Versus Daughters: Links to Adolescent Adjustment in Mexican Immigrant Families - Updegraff, Kimberly A. (2009)
Drawing on ecological and gender socialization perspectives, this study examined mothers’ and fathers’ relationships with young adolescents, exploring differences between mothers and fathers, for sons versus daughters, and as a function of parents’ division of paid labor. Mexican immigrant families (N = 162) participated in home interviews and seven nightly phone calls. Findings revealed that mothers reported higher levels of acceptance toward adolescents and greater knowledge of adolescents’ daily activities than did fathers, and mothers spent more time with daughters than with sons. Linkages between parent-adolescent relationship qualities and youth adjustment were moderated by adolescent gender and parents’ division of paid labor. Findings revealed, for example, stronger associations between parent–adolescent relationship qualities and youth adjustment for girls than for boys.